The Notary's Responsibility Regarding Deliberate Dishonesty Actions (Journal of Private and Commercial Law, 2022)
A notary is a public official who performs his or her position based on the authority given to him or her by the law. A notary declares and states the wishes of all parties in the authentic deed according to his or her legal knowledge. Prior to that, a notary has to make sure the deed does not violate the law, public order, or morality. One of the common problems with notarial deeds is when false statements are found in an authentic deed. The inclusion of false statements above into an authentic deed is a crime that is covered by Article 263 Paragraph (1) juncto Paragraph 264 Paragraph (1) of the Indonesian Criminal Law. This research is normative juridical research with a statutory approach and conceptual approach. The conclusion of this research is most of the false statements found in authentic deeds came from the parties interested in the deed; however, this does not mean a notary cannot be involved. Criminal law seeks material truth, and material truth cannot be assumed that the notary has only reiterated the wishes of the involved parties. The Notary may make two kinds of mistakes, intentionally or negligently. Therefore, it is necessary to distinguish between deliberate dishonesty and malpractice in notaries during their duties. A notary who intentionally submits false information to their deed the measures it called an act of deliberate dishonesty.